Migration as Investment: Empirical Tests of the Human Investment Approach to Geographical Mobility - Bowles, Samuel (The Review of Economics and Statistics, 1970)
T HE hypothesis that geographical mobility of workers is primarily a response to economic incentives arising from disequilibria across spacially separated labor markets has received considerable attention in the theoretical literature on investment in human beings.' In this paper I outline a simple model of migration as an economic process, and provide an empirical test of the model using data on net migration out of the United States South.2 To preview the main results, the model of migration as a response to economic incentive is supported. Specifically, the results suggest that the present value of the expected income gain from moving out of the South is positively related to the probability of moving and provides a better explanation of migration than the more conventional income measure based on regional differences in current incomes. Further, the level of schooling appears to increase the effect of income gain on the probability of moving, and age appears to reduce it. Significant racial differences in the main determinants of net migration are apparent.3